(untitled) (Proceedings of the Global Public Health Conference, 2023)
Ventilator-associated pneumonia has been a well-known complication in the intensive care unit (ICU) and continues to be a real threat in patients infected with coronavirus disease (COVID- 19), particularly in those that progress to acute respiratory distress syndrome (ARDS) with subsequent mechanical ventilation. Through a global perspective, this descriptive study was aimed at describing the patterns of co-infection with ventilator-associated pneumonia (VAP) in patients with COVID-19 ARDS. The global incidence rate of VAP in COVID-19 patients on mechanical ventilation was determined to be 41.2% supported by extended time spent on mechanical ventilation, increase in mortality rate, and the emergence of drug-resistant microbes. These outcomes are accompanied by the concomitant presence of previous antimicrobial use, invasive respiratory operations due to COVID-19 ARDS, and in some cases, corticosteroid treatment. The results of our findings add to the emergent threat of VAP as an important nosocomial infection as the COVID-19 pandemic persists.